2014
DOI: 10.1002/cbin.10244
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate exerts an anti‐immunosuppressive effect on cervical cancer by inhibiting PGE2 production and Foxp3 expression

Abstract: Artesunate (ART), derived from a common traditional Chinese medicine, has beeen used an antimalarial for several years. In this study, the effect and mechanism of ART on anti-human cervical cancer cells was examined. The level of prostaglandin E2 (PGE2 ) and the population of CD4+CD25+Foxp3 regulatory T cells (Treg) in peripheral blood were detected by flow cytometry. In vivo antitumor activity was investigated in mice with cervical cancer by the subcutaneous injection of various concentrations of ART. The con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 25 publications
0
33
0
Order By: Relevance
“…The general pattern of Treg depletion following artemisinin exposure was supported by Zhang et al. in their 2014 study that reported a similar depletion of CD4 + CD25 + FOXP3 + Treg in mouse cervical cancer models, with a corresponding inhibition of PGE 2 (prostaglandin E2) production and FOXP3 downregulation . This reduction in PGE 2 corroborates with a subsequent study in smooth muscle cells .…”
Section: Molecular Targets and Signaling Pathways Implicated In The Amentioning
confidence: 99%
“…The general pattern of Treg depletion following artemisinin exposure was supported by Zhang et al. in their 2014 study that reported a similar depletion of CD4 + CD25 + FOXP3 + Treg in mouse cervical cancer models, with a corresponding inhibition of PGE 2 (prostaglandin E2) production and FOXP3 downregulation . This reduction in PGE 2 corroborates with a subsequent study in smooth muscle cells .…”
Section: Molecular Targets and Signaling Pathways Implicated In The Amentioning
confidence: 99%
“…As an analog of ART, artesunate exerts better water solubility and higher oral bioavailability, due to its special structure with an additional hemisuccinate group that makes it a better candidate for cancer treatment [668]. The anti-cancer effects of artesunate have been demonstrated in bladder, breast, cervical, colorectal, esophageal, gastric, ovarian and prostate cancer, renal carcinoma, leukemia, melanoma and multiple myeloma [179,[669][670][671][672][673][674][675][676][677][678][679]. Its anti-cancer effects include induction of cell cycle arrest and apoptosis, inhibition of cell proliferation and growth, metastasis and angiogenesis [670,678,680].…”
Section: Artesunatementioning
confidence: 99%
“…However, in the present study, we used 20, 100, and 200 mg/kg of ART to treat rats with bladder cancer. Moreover, Zhang et al reported that ART at the dose of 50 and 100 mg/kg could inhibit the growth of cervical cancer, which resulted from inhibiting activity of regulatory T cells through PGE2 [25]. We speculate that the difference in the concentrations levels of ART necessary for malaria treatment compared to the treatment of tumors is due to ART not being attracted specifically to tumor sites.…”
Section: Resultsmentioning
confidence: 91%